2000
DOI: 10.1080/03091900050204287
|View full text |Cite
|
Sign up to set email alerts
|

Rotational laxity after anterior cruciate ligament injury by kinematic evaluation of clinical tests

Abstract: Despite the numerous studies on anterior cruciate ligament biomechanics and clinical tests, some disagreements still exist in the literature on the role of ACL in restraining rotations and which kinematic test after ACL injuries is the most suitable to evaluate this instability. This work analyses the capability of passive clinical and stress tests to detect an ACL state quantifying rotational instability. The study was conducted on animal knees with a new protocol. We found that an internal-external stress te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(35 reference statements)
3
5
0
Order By: Relevance
“…In the previously mentioned cadaveric study by Kato et al, ATT increased from ~4 to ~15 mm after complete ACL transection (65). These results corroborate observations in an earlier study by Zaffagnini et al, which demonstrated an increase in ATT from 4 mm in pigs with intact knees up to 16 mm following ACL transection (102). ACL transection also resulted in 4–20° of increased laxity in internal-external rotation in the pig knee (102).…”
Section: Biomechanicssupporting
confidence: 93%
See 2 more Smart Citations
“…In the previously mentioned cadaveric study by Kato et al, ATT increased from ~4 to ~15 mm after complete ACL transection (65). These results corroborate observations in an earlier study by Zaffagnini et al, which demonstrated an increase in ATT from 4 mm in pigs with intact knees up to 16 mm following ACL transection (102). ACL transection also resulted in 4–20° of increased laxity in internal-external rotation in the pig knee (102).…”
Section: Biomechanicssupporting
confidence: 93%
“…These results corroborate observations in an earlier study by Zaffagnini et al, which demonstrated an increase in ATT from 4 mm in pigs with intact knees up to 16 mm following ACL transection (102). ACL transection also resulted in 4–20° of increased laxity in internal-external rotation in the pig knee (102). Zaffagnini et al suggested, based on their findings in pigs, that evaluation of internal-external rotational laxity, in combination with anterior-posterior laxity, might be helpful in determining ACL status in the human (102).…”
Section: Biomechanicssupporting
confidence: 93%
See 1 more Smart Citation
“…But devices as the KT-1000 arthrometer [ 6 ] are limited to the anterior-posterior translation of the tibia, and studies call into question the intratester and intertester reliability of the device considered as a moderately reliable tool [ 7 , 8 ]. Although reconstructive surgery permits sufficient repair of this ligament [ 9 ] in the sagittal plane, it remains limited in the restoration of rotational stability and no reliable easy-to-use device to measure knee rotation is available [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many animal models have been proposed in the past [1, 15, 30, 41, 47, 77, 88, 98, 104, 105, 114, 116, 126, 127, 130] for the study of the injured knee. Especially the anatomy of the rabbit knee has been well defined and has been found to be comparable with that of the human [27, 35, 66, 97].…”
Section: Introductionmentioning
confidence: 99%